PENYULUHAN HUKUM PENCEGAHAN PENYALAHGUNAAN NARKOBA PADA REMAJA DI DESA KABINUANG - Amelia Putri Zalzabila Pakaya; Ananda Siti Nurbaiti (Makapande Mengabdi: Jurnal Ilmiah Pengabdian Kepada Masyarakat, 2025)
The use of drugs in Indonesia continues to rise, with many offenders coming from the younger population. Drug abuse among adolescents is a serious issue that can threaten the future of young generations as well as the social stability of society. Kabinuang Village in Dampal Utara District also faces this risk, making planned and sustainable preventive efforts necessary. The aim of this legal outreach activity is to enhance adolescents’ knowledge, awareness, and understanding of the dangers of drugs, applicable laws, and early prevention methods. This program is implemented through interactive lectures, group discussions, and Q&A sessions involving police officers and teachers. The results of this activity indicate an increase in adolescents’ understanding of the legal and social impacts of drug abuse, along with a shared commitment to protect the village from drug trafficking. Therefore, this legal outreach is expected to serve as an effective preventive measure to shield adolescents from the negative influence of drugs and strengthen social cohesion in Kabinuang Village.